The Clark International Airport ADPI phase 1 passenger terminal building - Chua, Andrew C.; Joson, Gerard Thomas F. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
For a nation heavily marketing itself as a favorable tourist destination; the country finds itself frequently struggling to provide adequate gateway facilities. More so with air liberalization policies that have been implemented in the recent years, the surging increase in the demand for air travel from passengers signals a great need for new airport facilities that would meet standards of modern civil aviation. In light of the issue, the Department of Transport and Communications (DOTC) and the Clark International Airport Corporation (CIAC) are investing towards the development of Clark into an aerotropolis, an international hub to serve alongside the NAIA Terminals. The company Aeroports de Paris Ingenierie (ADPI) has been commissioned for their multi-phase expansion proposal for the Clark International Airport in line with this greater development. The focus of this thesis shall be the design of a passenger terminal building that would mark the first in a series of development phases set in the master plan proposed by ADPI.
Includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Clark International Airport; Airport terminals -- Designs and plans; Airport facilities; Airports -- Philiippine -- Clark; Airport terminals -- Philippines -- Clark